1996
DOI: 10.1149/1.1836926
|View full text |Cite
|
Sign up to set email alerts
|

7Li ‐Nuclear Magnetic Resonance Observation of Lithium Insertion into Mesocarbon Microbeads

Abstract: The stacking order of graphite layers in mesocarbon microbeads (MCMB5) heat-treated between 700 and 3000°C was examined by analyses of x-ray diffraction measurements, and lithium insertion into the MCMBs has been observed using solid-state ti-nuclear magnetic resonance (7Li-NMR) spectroscopy. In MCMTBs heat-treated above 2000°C, the fully lithiated MCMBs showed two bands at ca. 45 ppm (vs. LiC1) and ca. 27 ppm in their 7Li-NMR spectra. The profile of the band at 45 ppm was very close to that for the first-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 5 publications
2
69
0
Order By: Relevance
“…Even at the SOC100 state, no peaks around −260 and −46 ppm were observed, indicating that there was no deposition of Li metal or cluster, as observed for hard carbons 47 , 48 , and the state of Li ions in GLG differed from that in LiC 6 49 . The peak position observed for GLG was rather similar to that observed for graphite with lower Li content or soft carbons prepared at lower temperatures 50 . In all cases, a broad peak was observed around 0 ppm and could be deconvoluted into 4 peaks at 11–12, 4–7, −1–1, and −1.4–1.5 ppm.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Even at the SOC100 state, no peaks around −260 and −46 ppm were observed, indicating that there was no deposition of Li metal or cluster, as observed for hard carbons 47 , 48 , and the state of Li ions in GLG differed from that in LiC 6 49 . The peak position observed for GLG was rather similar to that observed for graphite with lower Li content or soft carbons prepared at lower temperatures 50 . In all cases, a broad peak was observed around 0 ppm and could be deconvoluted into 4 peaks at 11–12, 4–7, −1–1, and −1.4–1.5 ppm.…”
Section: Resultssupporting
confidence: 77%
“…The contribution of peak “c’” was always small, and we assigned this peak to that from the Li ions in SEI because the thickness of the SEI layer is very small based on the XPS depth profiles of GLG at various states, as shown in Figs S2 – S13 . The Li filling density in GLG decreasing from peak “a” to peak “c” (a > b > c) depends on the chemical shrift 50 . The amount of Li ions was 6.1%, and the contribution of that providing peak “b” was the largest at the 1 st SOC50 state.…”
Section: Resultsmentioning
confidence: 99%
“…This is not beneficial towards safety for high power applications, such as in electric vehicles. An important part of Li is in a pseudometallic state 36. 37 For nanostructured carbons with very high specific surface areas, it is suggested that the storage capacity can be increased through the formation of Li 2 molecules between layers (Figure 5 b),38 by the presence of charged Li + clusters in the cavities (Figure 5 c),35 in the micropores, or in the inner space of CNTs, through the adsorption of Li ions on the surface and edges of graphite grains.…”
Section: Lithium‐ion Batteriesmentioning
confidence: 99%
“…[16] Ar ecent theoretical approach calculated the E A for Li hopping in LiC 6n ,b ased on Frenkel defects (0.42-0.52 eV) and Li vacancies( 0.42-0.56 eV). [17] Lithium intercalationi n MCMBw as investigatedw ith 7 Li NMR by Tatsumi et al [18] and two main signals (at 27 and 45 ppm) were observedf or the heat-treated samples (> 2000 8C). Below aheat-treatment temperature of 700 8C, the 7 Li signals shifted close to the 0-10 ppm range,e ven after full Li intercalation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent theoretical approach calculated the E A for Li hopping in LiC 6 n , based on Frenkel defects (0.42–0.52 eV) and Li vacancies (0.42–0.56 eV) . Lithium intercalation in MCMB was investigated with 7 Li NMR by Tatsumi et al . and two main signals (at 27 and 45 ppm) were observed for the heat‐treated samples (>2000 °C).…”
Section: Introductionmentioning
confidence: 99%